MHD pseudo-plastic nanofluid unsteady flow and heat transfer in a finite thin film over stretching surface with internal heat generation. (May 2015) - Lin, Yanhai; Zheng, Liancun; Zhang, Xinxin; Ma, Lianxi; Chen, Goong
Abstract: This paper investigates flow and heat transfer of magnetohydrodynamic (MHD) pseudo-plastic nanofluid in a finite film over unsteady stretching surface with internal heating effects. Four different types of nanoparticles, Cu, Al2 O3, CuO and TiO2 are considered with pseudo-plastic carboxymethyl cellulose (CMC)-water used as base fluids. The effects of power law viscosity on temperature fields are taken into account by assuming temperature field is similar to the velocity ones with modified Fourier's law of heat conduction for power-law fluids. Governing PDEs are reduced into coupled non-linear ODEs and solved numerically by shooting technique coupled with Runge–Kutta scheme and Newton's method. The effects of Hartmann number, power law index, unsteadiness parameter, thickness parameter and generalized Prandtl number on the velocity and temperature fields are presented graphically and analyzed in detail.